Master of orthopaedic surgery and traumatology workshop 2024 - Ahmad Shuhiamy, Norsaidatul Nadriah (Faculty of Medicine, 2024)
The groundwork for the Master of Orthopaedic Surgery and Traumatology program started in 2020. After four years of rigorous preparation, the Department of Orthopaedic Surgery and Traumatology will start the postgraduate program in June 2024.Accordingly, the department has organized a one-day workshop which was held on the 26th of April 2024. The workshop was targeted for orthopaedic lecturers to discuss the structure and implementation of the postgraduate program.